How Energy Secure is the Philippines? - Adoracion M. Navarro; Ma. Kristina P. Ortiz; Jethro El L. Camara (Philippine Institute for Development Studies (PIDS), 2023)
Energy security is a comprehensive concept and pursuing it as a developmental goal entails first and foremost a clearer understanding of what it means. This study proposes six broad elements in assessing energy security, namely, sufficiency, reliability, resilience, affordability, accessibility, and sustainability. In assessing the energy security situation in the Philippines, the study employs an indicators-based assessment. The method involves defining, based on existing literature, specific energy security indicators (ESIs) corresponding to the mentioned six broad elements and then running some calculations and conducting trends analysis using available data. The analyses of ESI trends over time and comparisons with other countries in Southeast Asia reveal notable findings, most of which are pointing to the current energy insecurity of the Philippines. The study then offers recommendations to improve energy security in the country and suggests that each element of energy security be considered an area of future research. As a demonstration of further scrutiny of an aspect of energy security, the study also examines energy sufficiency further by forecasting electric power demand and comparing the forecasts with the government's outlook on generating capacity up to 2028. The results highlight the necessity of timely investments on additional generating capacity and an efficient government permitting system.
Keywords: 330; energy security; energy self-sufficiency; energy reliability; energy system resilience; energy affordability; access to energy; energy sustainability; electricity demand forecasting; error correction model; elasticity-based model